Improving City Competitiveness for Economic Development and Job Creation : Philippines Urbanization Review Policy Notes (World Bank, Washington, DC, 2017)
This policy note presents an analysis of and recommendations on the city competitiveness improvement and is part of a broader Philippines urbanization study. The analysis draws on the competitive city framework which includes four pillars: 1. institutions and regulations; 2. infrastructure and land; 3. skills and innovation; 4. enterprise support and finance. It analyzes factors that constrain city competiveness, the role that city governments can play, and provides policy recommendations based on both the Filipino and international good practices in promoting city competitiveness. In addition, policy note studies the enabling environment at the national level to foster city competitiveness. Literature reviews, analysis of national level data and the results of firm level surveys and focus group meetings enrich the analysis. The policy note discusses 5 key challenges which affect economic development and job creation at the city level: 1) poor business environment; 2) weak infrastructure, land management and access to markets; 3) low demand for innovation and skill match; 4) access to finance and business support; and 5) inefficient economic planning, unclear mandate and weak governance. The analysis of these challenges is followed by a discussion of recommended priority actions. Despite a number of issues being addressed through reforms, more efforts are required at local and national level to improve the business environment, access to land and markets and upgrading of infrastructure, strengthening innovation systems and addressing skills mismatch, improving access to finance and business support services, and strengthening local institutions for economic development. Recommendations focus on areas which are most likely to offer quick results in terms of improving city competitiveness and where cities themselves have an important role to play as they are less dependent on national reforms. These include: 1. improving the business regulatory environment; 2. strengthening business support and innovation; 3. reforming institutions for economic development.